Holding up a Mirror to the Nonhuman Within: Karen Joy Fowler’s We Are All Completely Beside Ourselves - Lambert, Alice (FRAME, Journal of Literary Studies, 2026)
Kari Weil suggests that a “posthumanist autobiography” takes account of the nonhuman that is at the heart of the human author (93). Broadening her concept to include autobiografiction such as Karen Joy Fowler’s We Are All Completely Beside Ourselves, this paper contends that posthumanist autobiography is a powerful means of challenging our humanist mindset, encouraging the reader to explore the nonhuman within. In short, I argue that Fowler’s use of a posthumanist autobiographical mode forces the reader to recognise “humanity” as a social construct and consequently to rewrite their own sense of self.